DEVELOPING MATHEMATICAL REASONING THROUGH EMERGENT MODELING - Anwar, Lathiful (Jurnal Ilmiah AdMathEdu, 2012)
This paper discusses a design instructional which is called as Emergent Modeling within an exemplary instructional  sequence on data analysis. The modeling can be distinguished into both modeling as translation and modeling as organizing.  In this paper, the Emergent Modeling fits a modeling as organizing. In this perspective, the model and the situation modeled are mutually constituted in the process of modeling activity. The emergent has two meanings, it refers to both process by which models emerge, and the process by which these models support the emergence of more formal mathematical reasoning. The more formal is meant to refer to the constitution of new mathematical reality. This is reflected in the exemplary instructional sequence, in which the model coevolves with the notion of addition up to 100 as an entity. Key words : emergent modeling, model as organizing, more formal mathematical reasoning,                                 instructional sequence.